THE INFLUENCE OF THE CHRONOBIOLOGICAL FACTORS ON THE NUMBER OF HOMICIDES COMMITTED IN THE PLOVDIV DISTRICT OF THE REPUBLIC OF BULGARIA IN THE PERIOD 2008 – 2017 - Marin Baltov (Science & Research, 2019)

(untitled)
Chronobiological factors affect the behavior of people, especially those who commit homicides. Materials and methodology: The victims of 113 homicides committed in the Plovdiv District during the period 2008 – 2017 were studied. Their autopsies were carried out at the Forensic Medicine Department at Sveti Georgi University Multiprofile Hospital for Active Treatment – City of Plovdiv. The obtained results are processed statistically and are presented graphically. Most homicides occurred in the winter – 40 (35.40% ± 4.50%), and the least in the summer – 18 (15.04% ± 3.36%). The month with the highest concentration of homicides was January, during which 22 (19.47% ± 3.72%) homicides were committed. The least number of homicides occurred in July, when only 5 people lost their lives (4.42%). In the days of the week, most homicides were committed on Monday – 26 (23.00% ± 3.96%), and the least on Wednesday, Saturday and Sunday – 13. The distribution of homicides during the month showed that most homicides were committed in the middle of the month – from 11th to 20th – 45 (39.82% ± 4.60%).